The influence of oxidation on tribological properties of rapeseed oil - Kreivaitis, Raimondas; Padgurskas, Juozas; Gumbytė, Milda; Makarevičienė, Violeta; Spruogis, Bronislovas (Transport, 2011)
Approximately a half of all consumed lubricants, in one or another way, end up in the environment. Some countries put forward recommendations or even requirements for the use of environmentally friendly bio-lubricants the purpose of which is to reduce a negative influence of lubricants. The priority areas of using environmentally friendly lubricants cover water transport, hydraulic systems in forestry machinery, railway applications, road building machines etc. Particularly it is the case when an increased possibility of putting a lubricant in the environment occurs. Regarding good lubricity and excellent biodegradability, vegetable oils are widely used as environmentally friendly lubricants. The biggest disadvantage of vegetable oils as base stock for lubricants is pure oxidation stability. This article deals with the influence of thermal oxidation on tribological properties of rapeseed oil. The obtained results show that oxidation decreases lubrication ability due to structural changes in oil. The greatest negative influence of oxidation is obtained at the end of the induction period.First Published Online: 07 Jul 2011